Chemical vapor deposition growth of boron–carbon–nitrogen layers from methylamine borane thermolysis products. (11th December 2017) - Leardini, Fabrice; Flores, Eduardo; Galvis E, Andrés R; Ferrer, Isabel J; Ares, José Ramón; Sánchez, Carlos; Molina, Pablo; van der Meulen, Herko P; Navarro, Cristina Gómez; Polin, Guillermo López; Urbanos, Fernando J; Granados, Daniel; et al.
Abstract: This work investigates the growth of B–C–N layers by chemical vapor deposition using methylamine borane (MeAB) as the single-source precursor. MeAB has been synthesized and characterized, paying particular attention to the analysis of its thermolysis products, which are the gaseous precursors for B–C–N growth. Samples have been grown on Cu foils and transferred onto different substrates for their morphological, structural, chemical, electronic and optical characterizations. The results of these characterizations indicate a segregation of h-BN and graphene-like (Gr) domains. However, there is an important presence of B and N interactions with C at the Gr borders, and of C interacting at the h-BN-edges, respectively, in the obtained nano-layers. In particular, there is a significant presence of C–N bonds, at Gr/h-BN borders and in the form of N doping of Gr domains. The overall B:C:N contents in the layers is close to 1:3:1.5. A careful analysis of the optical bandgap determination of the obtained B–C–N layers is presented, discussed and compared with previous seminal works with samples of similar composition.